Análisis multitemporal del espejo de agua en la ciénaga de Zapatosa ubicada en los departamentos del Cesar y Magdalena, durante el periodo 2015 – 2017 y 2021 (2023)
The “Complejo Cenagoso Zapatosa” marshes in the departments of Cesar and Magdalena are considered to be one of the most important wetlands in Colombia. Due to environmental and sociological problems which have been unleashed upon the region over the last years it has been considerably affected by anthropoid interventions that alter its capacity to regulate its water flows. The implications of those changes are water shortages during times of drought and floodings during rainy seasons in populated areas. This thesis focuses on the multi temporal and spatial analysis of the Zapatosa Cenotage Complex. The analysis is carried out for the dry seasons between 2015 and 2017 as well as for the dry season of 2021.